2007
DOI: 10.1111/j.1528-1167.2007.01483.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal lobe epilepsy does not impair visual perception

Abstract: SUMMARYTemporal lobe epilepsy (TLE) can impair interictal cognitive function. In the perceptual domain, previous psychophysical studies demonstrated specific deficits in auditory and tactile perception in patients with TLE. This study compared performance of 25 TLE subjects and 27 controls on two low-level, visual tasks: luminance discrimination and frequency discrimination. Both tasks were performed under a relatively easy and a relatively difficult condition, by adjusting the stimulus duration. TLE subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 13 publications
(17 reference statements)
3
18
0
Order By: Relevance
“…In our fMRI study, the patients with mTLE presented increased functional connectivity within the primary visual cortex. Although it is not fully understood currently, our results at least support that the primary visual function in mTLE may not be reduced [23]. Moreover, an early study proposed that the patients with epilepsy may have hyperfunction in visual processing with enhanced prevalence in the epileptic hemisphere [38], although this hypothesis has been little supported by subsequent research (see review, [22]).…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…In our fMRI study, the patients with mTLE presented increased functional connectivity within the primary visual cortex. Although it is not fully understood currently, our results at least support that the primary visual function in mTLE may not be reduced [23]. Moreover, an early study proposed that the patients with epilepsy may have hyperfunction in visual processing with enhanced prevalence in the epileptic hemisphere [38], although this hypothesis has been little supported by subsequent research (see review, [22]).…”
Section: Discussionsupporting
confidence: 49%
“…4 Three-dimensional views of the results from group comparisons between the patients with mTLE and the controls, and the negative correlations between the epilepsy duration and mean z values within the RSN4 (green circle), the RSN5 (yellow circle), and the bilateral MT? areas (pink circle) addressed photosensitive epilepsy or occipital lobe epilepsy (see review, [22]), several psychobehavioral studies have found that the primary visual function is not impaired in mTLE [23,45]. Under the luminance and frequent discrimination stimuli, the performance of patients with mTLE did not show a difference from that of controls [23].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The results showed increases in connectivity in TLE in primary visual cortex, coupled with decreases in higher order visual processing regions such as MT+ when compared to controls that decreased with duration of disease. These findings may be consistent with behavioral results that showed no differences between reaction time or accuracy responding to visual stimuli in IGE (Verleger, et al 1997) or TLE (Grant, et al 2008); but deficits in processing of visual stimuli detected by EEG studies of visual evoked potentials (Lucking, et al 1970) and event-related potentials (Verleger, et al 1997). …”
Section: Perception and Attention Networksupporting
confidence: 78%